2022
DOI: 10.1186/s12864-022-09043-0
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of pre-mRNA alternative splicing regulated by m6A methylation in pig oxidative and glycolytic skeletal muscles

Abstract: Background Different types of skeletal myofibers exhibit distinct physiological and metabolic properties that are associated with meat quality traits in livestock. Alternative splicing (AS) of pre-mRNA can generate multiple transcripts from an individual gene by differential selection of splice sites. N6-methyladenosine (m6A) is the most abundant modification in mRNAs, but its regulation for AS in different muscles remains unknown.  Results We char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
(108 reference statements)
2
1
0
Order By: Relevance
“…The study found that the most abundant types of ASEs in all tissues were MEX and SE, consistent with other studies’ findings [ 26 , 27 ]. The common ASGs in the eight tissues accounted for 63.21–76.13% of each tissue, indicating a certain degree of conservation in the genes undergoing ASEs across tissues.…”
Section: Discussionsupporting
confidence: 92%
“…The study found that the most abundant types of ASEs in all tissues were MEX and SE, consistent with other studies’ findings [ 26 , 27 ]. The common ASGs in the eight tissues accounted for 63.21–76.13% of each tissue, indicating a certain degree of conservation in the genes undergoing ASEs across tissues.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, 40,052 selective shearing events corresponding to 9369 genes indicate that selective shearing genes are prevalent before and after adipocyte differentiation, with skipped exons being the most abundant type of selective shearing, similar to that reported in other livestock animals [15][16][17].…”
Section: Discussionsupporting
confidence: 85%
“…Several studies report an association between m 6 A levels and alternative mRNA splicing [51,52] including the adenovirus transcriptome [53], although the underlying mechanisms were not elucidated. Long read sequencing identified the BCP-RNAs and we mapped two pC transcripts (pC-Long (L) or pC-Short (S)), pgRNA and a number of spliced RNAs which encode the 5' stem-loop DRACH motif (Fig 4D and S1 Table).…”
Section: Mapping the Hypoxic Hbv Transcriptome And Impact Of M 6 A Mo...mentioning
confidence: 99%